An analysis of J.S. Bach’s Partita in B flat major, BWV 825; W.A. Mozart’s Piano Sonata in D major, K.576; F. Chopin’s Mazurkas, Opus 17; A. Khachaturian’s Toccata: theoretical, stylistic, and historical background - Kim, Jung Won (Kansas State University, 2015)
This Master’s report analyzes four piano compositions performed on April 9, 2015 at the author’s Master’s recital. The works under consideration are Johann Sebastian Bach’s Partita in B flat major, BWV 825; Wolfgang Amadeus Mozart’s Piano Sonata in D major, K.576; Fryderyk Chopin’s Four Mazurkas, Opus 17; and Aram Khachaturian’s Toccata. This analysis includes the discussion of the theoretical, stylistic, and historical background of each composition.
Keywords: Bach Partita in B-flat major; Mozart Piano Sonata in D-major K.576; Chopin Mazurka Op.17; Khachaturian Toccata; Music (0413)